Short Communication: Adoption level of indigenous communities on agricultural technology in East Kalimantan, Indonesia: Problem and adaptive solutions - Ndan Imang (Society for Indonesian Biodiversity, 2020)
Abstract. Imang N. 2020. Short Communication: Adoption level of indigenous communities to agricultural technology: problem and adaptive solutions in East Kalimantan, Indonesia. Biodiversitas 21: 1160-1164. The economic and cultural background of the indigenous people of the Dayak Borneo was traditional shifting cultivation, hunting, and gathering. Since the 1980s, Indonesian central government promoted Resettlement Program by relocating them in down rivers to encourage and to improve their agricultural and economic life. By living in downriver with limited farming areas, they, of course, need more products of agriculture and therefore government promoted agricultural extension. The objectives of the study are to: assess adoption level of two indigenous Dayak communities on agricultural technology, assess the causes of problems on adoption of agricultural technology, and seek adaptive strategy in implementing agricultural technology. Data were collected by interviewing 54 respondents that were selected randomly and descriptive qualitative approach was used for data analysis. Some important findings were: (i) adoption level of 60% i.e. Low level and 40% i.e. middle level in both villages; (ii) the low level of adoption was caused by some factors, such as: low performance of the extension officers which was caused by the lack support from government, and the background of the farmers; farmers with low education background need visual media to understand the extension and to see the evidence of the new technology; (iii) adaptive strategies to improve agricultural extension level such as: government should support the extension officers with appropriate visual and material support such as LCD projector, portable generator, appropriate training and communication skill that suitable with socio-cultural background of the respondents. The extension officers also need to understand the cultural background of the respondents. Practical implication is that the government can develop more typical effective method of extension for indigenous communities with low educational background and traditional way of agriculture. Theoretical implications, of course, are to provide specific further information for research related to agricultural extension.